2006
DOI: 10.1038/sj.onc.1209431
|View full text |Cite
|
Sign up to set email alerts
|

Decreased intranuclear mobility of acute myeloid leukemia 1-containing fusion proteins is accompanied by reduced mobility and compartmentalization of core binding factor β

Abstract: Acute myeloid leukemia 1 (AML1) gene on chromosome 21 is involved in several chromosomal translocations, including t(8;21) and t(16;21), that produce chimeric fusion proteins AML1-eight twenty-one (ETO) and AML-myeloid transforming gene chromosome 16 (MTG16), which contribute to leukemogenesis. The molecular basis for the leukemogenic effects of these fusion proteins is incompletely understood. Using gel-shift assay, we showed that AML1-ETO and AML1-MTG16 bound to a series of AML1 consensus DNA-binding sites w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…In our previous studies (Dong et al, 2004;Qiu et al, 2006), the decreasing intranuclear mobility of leukemia-related fusion proteins resulting from chromosomal translocation in acute myeloid leukemia (AML), namely PML-RARa or AML1-ETO, has been demonstrated compared with wild-type RARa or AML1, respectively. The CC domain of PML, like in PML-RARa oncogenic chimeric protein (Huang et al, 2008), was also shown to be responsible for the reduction of intranuclear mobility of PAX5-PML, implying its importance for this effect.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In our previous studies (Dong et al, 2004;Qiu et al, 2006), the decreasing intranuclear mobility of leukemia-related fusion proteins resulting from chromosomal translocation in acute myeloid leukemia (AML), namely PML-RARa or AML1-ETO, has been demonstrated compared with wild-type RARa or AML1, respectively. The CC domain of PML, like in PML-RARa oncogenic chimeric protein (Huang et al, 2008), was also shown to be responsible for the reduction of intranuclear mobility of PAX5-PML, implying its importance for this effect.…”
Section: Discussionmentioning
confidence: 99%
“…A rectangular region in the nucleus was bleached by applying maximal laser power for approximately 1 s. In all FRAP experiments, only cells expressing low levels of protein were examined to avoid artifacts of overexpression as previously described by us (Dong et al, 2004;Qiu et al, 2006). Figure 5 shows images taken right before bleaching (prebleach), immediately after bleaching (bleach) and at several time points after bleaching.…”
Section: The Intranuclear Mobility Of Pax5-pml Is Decreased Compared mentioning
confidence: 99%
See 3 more Smart Citations